2019
DOI: 10.3390/genes10040279
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Differences between 4-Year-Old Monozygous Male Twins Mosaic for Normal, Premutation and Fragile X Full Mutation Alleles

Abstract: : This study describes monozygotic (MZ) male twins with fragile X syndrome (FXS), mosaic for normal size (NS: <44 CGGs), premutation (PM: 55–199 CGG) and full mutation (FM alleles ≥ 200) alleles, with autism. At 4 years of age chromosomal microarray confirmed monozygosity with both twins showing an XY sex complement. Normal size (30 CGG), PM (99 CGG) and FM (388–1632 CGGs) alleles were detected in Twin 1 (T1) by standard polymerase chain reaction (PCR) and Southern blot testing, while only PM (99 CGG) and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Similar reverted and non-mosaic alleles have been described in FXS families both in unaffected females [19,22] and in unaffected males [23,24]. Contracted alleles in the range of normality have also been detected along with expanded ones in FXS mosaic males, such as in the four affected boys reported by Maia et al [25], who inherited the normal allele by their FM or PM mother, or as in a monozygous male twin, who derived the normal allele from his PM mother [26]. These latter cases are probably due to somatic instability of the CGG expansions in the range of PM or FM, which is well documented [27,28], while information regarding unstable normal alleles is limited [29].…”
Section: Discussionsupporting
confidence: 65%
“…Similar reverted and non-mosaic alleles have been described in FXS families both in unaffected females [19,22] and in unaffected males [23,24]. Contracted alleles in the range of normality have also been detected along with expanded ones in FXS mosaic males, such as in the four affected boys reported by Maia et al [25], who inherited the normal allele by their FM or PM mother, or as in a monozygous male twin, who derived the normal allele from his PM mother [26]. These latter cases are probably due to somatic instability of the CGG expansions in the range of PM or FM, which is well documented [27,28], while information regarding unstable normal alleles is limited [29].…”
Section: Discussionsupporting
confidence: 65%
“…Previous studies have also reported the associations of mosaicism type with cognitive and behavioral outcomes. Data consistently show an inverse correlation between methylation level and intellectual functioning, (Basuta et al, 2015;Hagerman et al, 1994;Pandelache et al, 2019;Pretto, Yrigollen, et al, 2014;Wöhrle et al, 1998) with males with FXS having completely or near completely unmethylated full-mutation alleles showing typical intellectual development (Basuta et al, 2015;Hagerman et al, 1994;Wöhrle et al, 1998). On the other hand, studies on size mosaicism have arrived at mixed conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the level of FXS protein, FMRP, is correlated with IQ ( 139 , 140 ), but the relation with other phenotypes is not as clear. In addition, mosaicism will influence phenotypic severity for IQ and potentially other phenotypes, but this is not well-understood ( 141 , 142 ). Gene dosage has variable effects on the efficacy of a drug and the expression levels of different phenotypic traits in an individual.…”
Section: Discussionmentioning
confidence: 99%